De la systématisation de Bucarest à la destruction des villages roumains - Bogdan Andrei Fezi (In Situ)
On the field prepared by the collectivization and by the Soviet political repression in Romania, Ceausescu planned, starting from 1965, to “systematize” the Romanian villages. The project intended to demolish a third of 13,123 villages and finally to better organize the control over the population. After the savage demolitions of a large part of the historic centre of Bucharest, Romanian and international reactions against the villages “systematization” stopped this genocide of the Romanian countryside on the eve of the dictator’s fall, in 1989.